2011
DOI: 10.1073/pnas.1113324109
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution dose–response screening using droplet-based microfluidics

Abstract: A critical early step in drug discovery is the screening of a chemical library. Typically, promising compounds are identified in a primary screen and then more fully characterized in a dose-response analysis with 7-10 data points per compound. Here, we describe a robust microfluidic approach that increases the number of data points to approximately 10,000 per compound. The system exploits Taylor-Aris dispersion to create concentration gradients, which are then segmented into picoliter microreactors by droplet-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
219
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(225 citation statements)
references
References 47 publications
3
219
0
3
Order By: Relevance
“…Cefsulodin is also quite selective for SHP2, displaying, with one exception of SHP1, >10-fold selectivity against all PTPs examined ( Table 1). As reported before, 12 cefsulodin also exhibits inhibitory activity against PTP1B, although with much less potency compared to SHP2 (Table 1).…”
supporting
confidence: 75%
“…Cefsulodin is also quite selective for SHP2, displaying, with one exception of SHP1, >10-fold selectivity against all PTPs examined ( Table 1). As reported before, 12 cefsulodin also exhibits inhibitory activity against PTP1B, although with much less potency compared to SHP2 (Table 1).…”
supporting
confidence: 75%
“…Droplet microfluidics has shown promise in various fields including directed evolution, 1,2 drug screening, 3,4 and droplet-based nucleic acid analysis. 5,6 Compartmentalization of reactions in small droplets using the microfluidic method increases the sensitivity of assays and reduces the cost.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, Song et al [17], Damean et al [18], Niu et al [19], Sun et al [20], Wang et al [21] and Agresti et al [22] reported systems to generate sequences of droplets scanning concentrations of one substance (up to four orders of magnitude) and used them to screening of biochemical reactions. Miller et al [23] demonstrated a microfluidic system that exploits Taylor-Aris dispersion to create a concentration gradient within about 10,000 droplets per compound. Guo et al [24] presented an optofluidic device for real-time, high-throughput (2000 droplets per second) quantitative analysis of droplet contents.…”
Section: Introductionmentioning
confidence: 99%